Advanced Biotechnologies: Collections of Plant Cell Cultures As a Basis for Development and Production of Medicinal Preparations - Popova, E. V.; Nosov, A. V.; Titova, M. V.; Kochkin, D. V.; Fomenkov, A. A.; Kulichenko, I. E.; Nosov, A. M.
The review examines the principles in formation of cell culture and tissue collections of higher plants in vitro as a variant of genetic collections, the modern state and perspective of using collections in studies of the peculiarities and patterns of synthesis of biologically active substances of higher plants, the important role of collections in biotechnological production of substances for medicinal preparations, and methods for maintaining the stability of cell cultures during long-term cultivation. Particular attention is paid to the retrospective and current state of the All-Russia Collection of Cell Cultures of Higher Plants, the founder of which was Russian Academy of Sciences Corresponding Member R.G. Butenko.
Keywords: BIOBANKING; BIOLOGICALLY ACTIVE SUBSTANCES; BIOTECHNOLOGY; SECONDARY METABOLISM; GENETIC COLLECTIONS; CRYOPRESERVATION; CELL CULTURES